Non-contact measurement of facial surface vibration patterns during singing by scanning laser Doppler vibrometer - Kitamura, Tatsuya; Ohtani, Keisuke (Frontiers in Psychology, 2015)
This paper presents a method of measuring the vibration patterns on facial surfaces by using a scanning laser Doppler vibrometer (LDV). The surfaces of the face, neck, and body vibrate during phonation and, according to Titze (2001), these vibrations occur when aerodynamic energy is efficiently converted into acoustic energy at the glottis. A vocalist's vibration velocity patterns may therefore indicate his or her phonatory status or singing skills. LDVs enable laser-based non-contact measurement of the vibration velocity and displacement of a certain point on a vibrating object, and scanning LDVs permit multipoint measurements. The benefits of scanning LDVs originate from the facts that they do not affect the vibrations of measured objects and that they can rapidly measure the vibration patterns across planes. A case study is presented herein to demonstrate the method of measuring vibration velocity patterns with a scanning LDV. The objective of the experiment was to measure the vibration velocity differences between the modal and falsetto registers while three professional soprano singers sang sustained vowels at four pitch frequencies. The results suggest that there is a possibility that pitch frequency are correlated with vibration velocity. However, further investigations are necessary to clarify the relationships between vibration velocity patterns and phonation status and singing skills.